Vključevanje digitalne tehnologije pri ponavljanju in utrjevanju znanja pri pouku angleščine v 3. razredu - Fras, Mirjana (Revija inovativna pedagogika, 2025)
Teaching foreign languages in the early years of primary school must be engaging and appealing to spark the pupils' curiosity and willingness to participate in lessons. By using various teaching methods and approaches, the integration of digital technology can serve as a significant motivational factor in language learning. This paper focuses on the use of innovative teaching approaches that incorporate digital technology in revising and consolidating learning material. The aim is to provide English teachers in the first three grades with ideas on how to conduct revision and consolidation activities in a way that fosters greater pupil engagement and motivation. The research was conducted using a case study. Data was collected through unstructured observations during a lesson. Grade 3 pupils consolidated their knowledge through station-based learning, movement, and the use of interactive screen and tablet applications. Each station offered different tasks, educational games, or applications designed to help pupils revise and consolidate vocabulary, participate in conversations, answer questions, and form sentences independently. The findings showed that all pupils remained actively engaged and motivated throughout the lesson. They followed the instructions, promptly transitioned between stations without additional reminders, successfully completed the tasks, and received immediate feedback or were presented with correct answers at the end of the lesson. The pupils perceived station-based learning with diverse activities not as traditional learning but as play. This approach to revising and consolidating could, in the long term, lead to improved academic performance and, consequently, more active foreign language proficiency.
Keywords: active learning; aktivno učenje; Angleščina; delo po postajah; digital technology; Digitalna pismenost; digitalna tehnologija; innovative teaching approaches; inovativni učni pristopi; Osnovnošolsko izobraževanje; station-based learning